Can suffixal augmentation express approximation? The case of denominal evaluative nouns - Dejan Stosic; Dany Amiot (Zeitschrift für Wortbildung)
The paper focuses on the relationships between so-called diminutive/augmentative morphology and approximation. As this topic is very broad, only the denominal nouns are studied in this article. Our study, based on data from French and Serbian, has a twofold aim: to answer the question asked in the title of this article and, the answer being negative, try to understand why only diminutive suffixes, and not augmentative ones, can express approximation. This should also allow us to understand the specificity of diminutive approximation. Firstly, we show that even though both types of evaluatives express non-conformity with respect to a norm, in the case of diminution the norm is not reached, whereas augmentation entails that the norm is not only reached but is exceeded. This suggests that approximation is fundamentally associated with a certain degree of deficiency, which is consistent with the literature on this topic. Secondly, we demonstrate that the main peculiarity of diminutive approximation is that it is measurative in nature as it is underlined by the orientational metaphor up/down and based on a set of gradable semantic dimensions such as small/big, few/much. This is not the case of other morphological devices that trigger approximative meanings (e.g., pseudo-, -oïde), whose role is to provide a global evaluation of the matching between a given referent and core members of the category expressed by the base.